Kebebasan Beribadat Dan Penerapan Peraturan Menteri Tentang Rumah Ibadat Di Kota Kupang - E. Natonis, Ismail; Y. Stefanus, Kotan.; Kosmas, Ebu (CV. Multi Kreasi Media, 2024)
Freedom of worship is guaranteed by the 1945 Constitution and regulated in statutory regulations to prevent conflict between religious communities. The government issued Joint Regulations of the Minister of Home Affairs and the Minister of Religion Number 8 and 9 of 2006 concerning the Establishment of Houses of Worship as a reference in Indonesia, including in the City of Kupang. This research aims to analyze the meaning of freedom of worship from the perspective of human rights and law as well as the application of the 2006 PBM in the establishment of places of worship in Kupang City. The research method uses an empirical juridical and formal juridical approach, by analyzing field data and legal sources. The results of the research show that the fulfillment of the right to worship is implemented by the Ministry of Religion of Kupang City and other stakeholders through PERBER 2006 education, conflict mediation, and providing legal certainty. Implementation of PERBER 2006 is supported by regulations from the Mayor of Kupang and synergy with other stakeholders. To prevent conflict and increase understanding of PERBER 2006, synergy with stakeholders and local wisdom-based conflict resolution models are needed.